Analysis of Learning Style Characteristics of Class X2 Students in Biology Subject at SMA Negeri 2 Sukoharjo - Yana, Dwi Yovi (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
Student has different characteristics in receiving an education and teaching, including different learning styles. Learning styles owned by students affect the achievement of learning objectives. A teacher needs to understand the learning styles of students in order to create effective learning. The purpose of this study was to determine the learning styles of students. The subjects of this research were X grade students of senior high school Sukoharjo. The research method used in this research is descriptive qualitative. Data collection in this study was carried out using observation instruments and questionnaires about learning styles. Observations were made and the learning style questionnaire was filled in by 33 class X students. The data from observations and filling out the questionnaire were analyzed using the percentage method and then described. The results of the analysis of learning styles show that there are 3 types of learning styles in class X2, namely visual, auditory and kinesthetic learning styles. The tendency of the learning style of class X2 students is kinesthetic learning style with a percentage of 61%.Keywords: learning styles, visual, auditory, kinesthetic